2019
DOI: 10.1029/2019jc015307
|View full text |Cite
|
Sign up to set email alerts
|

Study of Lateral Flow in a Stratified Tidal Channel‐Shoal System: The Importance of Intratidal Salinity Variation

Abstract: Lateral flow significantly contributes to the near-bottom mass transport of salinity in a channel-shoal system. In this study, an integrated tripod system was deployed in the transition zone of a channel-shoal system of the Changjiang Estuary (CE), China, to observe the near-bottom physics with high temporal/spatial resolution, particularly focusing on the lateral-flow-induced mass transport. These in situ observations revealed a small-scale salinity fluctuation around low water slack during moderate and sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…To demonstrate the influence of groynes, the nearest groyne to the observational site was removed in the model. Earlier work (Figure 14 in Zhou et al (2019)) showed that such removal strongly reduced lateral flow during LWS. By keeping or removing the nearest groyne, we therefore have two cases with (Case 0) or without (Case 1) lateral flow during LWS, which can be used to quantify the effect of this groyne-induced impacts on lateral flow and sediment transport.…”
Section: Effect Of Groyne Removalmentioning
confidence: 86%
See 3 more Smart Citations
“…To demonstrate the influence of groynes, the nearest groyne to the observational site was removed in the model. Earlier work (Figure 14 in Zhou et al (2019)) showed that such removal strongly reduced lateral flow during LWS. By keeping or removing the nearest groyne, we therefore have two cases with (Case 0) or without (Case 1) lateral flow during LWS, which can be used to quantify the effect of this groyne-induced impacts on lateral flow and sediment transport.…”
Section: Effect Of Groyne Removalmentioning
confidence: 86%
“…The present study further supports the importance of lateral salinity gradient to sediment transport, and particularly focuses on lateral salinity gradient during high and low water slack. Zhou et al (2019) reported a salinity-induced density gradient and the lateral flow thereon due to retention of high-salinity water by groynes. This companion study further investigated the lateral sediment transport due to this lateral flow during LWS, and also expanded findings to lateral process during HWS, extending our understanding of slack-water dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lateral circulation and lateral sediment transport have received increasing attention because lateral processes appear to play important roles in exchange flow (Cheng et al, 2017; Cheng & Valle‐Levinson, 2009; Lerczak & Rockwell Geyer, 2004; M. Li et al, 2014; Scully et al, 2009), estuarine stratification (Aristizábal & Chant, 2014; Scully & Geyer, 2012), and sediment trapping (Fugate et al, 2007; Huijts et al, 2006; Kim & Voulgaris, 2008; Lacy et al, 2014; Ralston et al, 2012). Several mechanisms have been proposed that drive lateral flows, including differential advection (Huijts et al, 2009, 2011; Lerczak & Rockwell Geyer, 2004; Nunes & Simpson, 1985), Ekman forcing (Cheng et al, 2017; Huijts et al, 2006), diffusive boundary layers (Chen & Sanford, 2009; Garrett et al, 1993), cross‐stream density gradients (Chen & Sanford, 2009; Scully et al, 2009; Zhou et al, 2019), channel curvature (Chant, 2002; Kim & Voulgaris, 2008), and wind forcing (Chen et al, 2009; Y. Li & Li, 2011) and interaction between barotropic tides and bathymetry variations in cross section (Valle‐Levinson et al, 2000; Zhu et al, 2018). In estuaries with lateral variations of bathymetry, these mechanisms compete with or reinforce each other.…”
Section: Introductionmentioning
confidence: 99%